FRI0187 Lipoprotein (A) and possible related factors in patients with spondyloarthritis. results of the carma study. (12th June 2018) - García-Gómez, C.; Martín-Martínez, M.; Fernández-Carballido, C.; Castañeda, S.; González-Juanatey, C.; González Fernández, M.; Sanmartí, R.; García Vadillo, J.; Fernández Gutiérrez, B.; García Arias, M.; Manero, F.; Senabre, J.; et al.
Abstract : Background: Cardiovascular disease (CVD) is the main cause of mortality and morbidity in patients with spondyloarthritis (SpA), partially explained by traditional CV risk factors (CVRF). Other non-conventional CVRF, probably related to chronic systemic inflammation, may be involved. In this sense, lipoprotein (a) [Lp (a)], an non-conventional risk factor with proatherogenic and thrombogenic properties, could be involved, since it seems to act as an acute-phase reactant, there are few data on this aspect in these patients. Objectives: To evaluate the prevalence of hyperlipoproteinemia (a) in patients with SpA and analyse the possible related factors. Methods: Analysis of the baseline visit of patients with ankylosing spondylitis (AS) and psoriatic arthritis (PsA) of the CARMA project (CARdiovascular in Reumatology), a prospective cohort study of 10 years of follow-up, to evaluate the cardiovascular risk in chronic rheumatic inflammatory diseases, including rheumatoid arthritis, AS and PsA, followed in 67 Spanish rheumatology centres. A multivariate logistic regression model was performed, in which the dependent variable was hyperliproteinemia (a), defined as the plasma concentration of lipoprotein (a) [Lp (a)]≥50 mg/dl. Sociodemographic factors and those related to the disease itself have been included as independent variables. Results: 1459 patients were analysed, 738 with AS and 721 with PsA. Plasma concentrarions of Lp(a) were available in 57.7% of the patients with AS and in 57.1% of the patients with PsA. A 19.2% (95% CI: 16.80–22.05) of the patients with SpA, 20.7% (95% CI: 16.91–24.82) of AS and 17.7% (95% CI: 14.15–21.75) of PsA, respectively, had hyperlipoproteinemia (a), without statistically significant differences with respect to the control group: 16.7% (95% CI: 13.23–20.86; p=0.326). After adjusted for age and sex, only patients with AS were more likely to have hyperlipoproteinemia (a) than the control grup (OR: 1.806, 95% CI: 1177–2.771, p=0.007). In the model adjusted for possible confounding factors, high values of apolipoprotein B in all patients, non-steroidal anti-inflammatories in AS, and sex (men) and kidney disease as comorbidity in PsA, were associated with a higher probability of presenting hyperlipoproteinemia (a). Conclusions: Patients with AS have a higher percentage of hyperlipoproteinemia (a) compared to the control group. No specific factors of the disease have been identified that are associated with hyperlipoproteinemia (a) in each of the analysed groups. Disclosure of Interest: None declared